Influence of sugar cane vinasse on the sorption and degradation of herbicides in soil under controlled conditions - Lourencetti, Carolina [UNESP]; Marchi, Mary Rosa Rodrigues de [UNESP]; Ribeiro, Maria L. (Taylor & Francis Inc, 2012)
This study reports the influence of sugar cane vinasse on the persistence, sorption and leaching potential of diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea), hexazinone (3-cyclohexyl-6-(dimethylamino)-1-methyl-1,3,5-triazine-2,4-dione) and tebuthiuron (1-(5-tert-butyl-1,3,4-thiadiazol-2-yl)-1,3-dimethylurea) in both a clay and sandy soil from a tropical area of Brazil. The experiments were conducted out under controlled laboratory conditions. The addition of sugarcane vinasse to soil influenced the persistence and sorption of the herbicides in both the studied clay and sandy soils, with a considerable decrease in the diuron DT50 values in clay soil. The Ground Water Ubiquity Score (GUS) Index classifies the herbicides as leachers in both soils and treatments, with the exception of diuron, which is classified as a non-leacher in clay soil-vinasse and as a transient herbicide in sandy soil. These results suggest that special attention should be given to areas such as those where the sandy soil was collected in this study, which is a recharge area of the Guarani Aquifer and is likely to experience groundwater contamination due to the high leaching potential of the applied pesticides.
Keywords: Herbicides; sugar cane vinasse; sorption; degradation; leaching potential; soil